Two-Year Clinical and Functional Outcomes of an Asian Cohort at Ultra-High Risk of Psychosis - Chan, Chun Ting; Abdin, Edimansyah; Subramaniam, Mythily; Tay, Sarah Ann; Lim, Lay Keow; Verma, Swapna (Frontiers in Psychiatry, 2019)
Aims To determine the 2-year clinical and functional outcomes of an Asian cohort at ultra-high risk (UHR) of psychosis. Method This was a longitudinal study with a follow-up period of 2 years on 255 help-seeking adolescents and young adults at ultra-high risk of psychosis managed by a multi-disciplinary mental health team in Singapore. Clients received case management, psychosocial and pharmacological treatment as appropriate. Data comprising symptom and functional outcomes were collected over the observation period by trained clinicians and psychiatrists. Results The 2-year psychosis transition rate was 16.9%, with a median time to transition of 168 days. After 2 years, 14.5% of the subjects had persistent at-risk symptoms while 7.5% developed other non-psychotic psychiatric disorders. 38.4% of the cohort had recovered and was discharged from mental health services. The entire cohort’s functioning improved as reflected by an increase in the score of the Social and Occupational Functioning Assessment Scale during the follow-up period. Predictors to psychosis transition include low education level, baseline unemployment, a history of violence and Brief Limited Intermittent Psychotic Symptoms, while male gender predicted the persistence of UHR state or the development of non-psychotic disorders. Conclusion Use of the current UHR criteria allows us to identify individuals who are at imminent risk of developing not just psychosis, but also those who may develop other mental health disorders. Future research should include identifying the needs of those who do not transition to psychosis, while continuing to refine on ways to improve the UHR prediction algorithm for psychosis.